Nonlinear evolution of ion acoustic solitary waves in space plasmas: Fluid and particle-in-cell simulations - Kakad, Bharati; Kakad, Amar; Omura, Yoshiharu (My University, 2014)
Spacecraft observations revealed the presence of electrostatic solitary waves (ESWs) in various regions of the Earth's magnetosphere. Over the years, many researchers have attempted to model these observations in terms of electron/ion acoustic solitary waves by using nonlinear fluid theory/simulations. The ESW structures predicted by fluid models can be inadequate due to its inability in handling kinetic effects. To provide clear view on the application of the fluid and kinetic treatments in modeling the ESWs, we perform both fluid and particle-in-cell (PIC) simulations of ion acoustic solitary waves (IASWs) and estimate the quantitative differences in their characteristics like speed, amplitude, and width. We find that the number of trapped electrons in the wave potential is higher for the IASW, which are generated by large-amplitude initial density perturbation (IDP). The present fluid and PIC simulation results are in close agreement for small amplitude IDPs, whereas for large IDPs they show discrepancy in the amplitude, width, and speed of the IASW, which is attributed to negligence of kinetic effects in the former approach. The speed of IASW in the fluid simulations increases with the increase of IASW amplitude, while the reverse tendency is seen in the PIC simulation. The present study suggests that the fluid treatment is appropriate when the magnitude of phase velocity of IASW is less than the ion acoustic (IA) speed obtained from their linear dispersion relation, whereas when it exceeds IA speed, it is necessary to include the kinetic effects in the model.
Keywords: Ion acoustic solitary waves; Space plasmas; Electrostatic solitary waves; PIC simulations; Initial density perturbation; IASW